Exclusión de la antijuricidad de la conducta en actos de servicio en defensa de un derecho propio o ajeno en el cumplimiento del deber legal de las fuerzas armadas cuando actúan en el marco de estados de excepción y ejerzan funciones relacionadas con la seguridad interna. - Hurtado Macas, Shakira Kimberly (2022)
In this Curriculum Integration Work Report “Exclusion of Unlawful Conduct in Acts of Service in Defense of Their own or Other Rights in the Fulfillment of the Legal Duty of the Armed Forces When They Act in the Framework of States of Exception and Exercise Functions Related to Internal Security.” It was born as a response to the need to study one of the problems that has been most evident in recent years in our state, and that is directly related to the need to ensure the actions of the armed forces when they provide support. in the mission of the national police with regard to State security, since the Comprehensive Organic Criminal Code only justifies the actions of the national police and prison guides in internal security, despite the fact that the need for that the different state security institutions work together, in this case with the support of the armed forces, in internal security. The present investigation is made up of an analysis of necessary topics and necessary doctrine to justify that the lack of the same protection enjoyed by the national police in internal security affects the effective action of the armed forces to protect citizens, in Regarding legal protection in the prosecution of acts that damage harmony in society and therefore the subjects that comprise it. The information obtained from national legislation, as well as from other countries, must be optimal to ensure the protection of this security group, so there are legal provisions related to not prosecuting a national security server when, in pursuit of their mission, they are defending a own right or someone else's. The study of comparative law, although somewhat limited, has been of great contribution to this investigation since it considers the importance, and embraces, the joint work of the institutions in charge of internal security or public order. In the same way, the application of methods such as interviews and surveys with the collaboration of professional personnel knowledgeable about the law, support this aspiration since they consider that our Comprehensive Criminal Organic Code should consider the members of the armed forces in their joint actions. with the national police, among the subjects who enjoy exclusion from illegality in our country, not only as citizens but also as servants of the public sector. 5 The reality of the problem that corresponds to a legal and social nature, is manifest, therefore, it has captured our personal interest, in addition to having to be the object of interest of the Ecuadorian state as the main protector of social harmony and holder of punitive power, for which it is consolidates the need to propose a reform to the Comprehensive Organic Criminal Code, where legal certainty is protective of the actions of the armed forces when they act in favor of public safety, with them the rights of the members of the armed forces are guaranteed, the committing harmful acts, and efforts aimed at safeguarding assets protected by the state, society and its harmony are reinforced.